EFFECT OF ESTRUS SYNCHRONIZATION PROTOCOLS INCLUDING PGF2α AND GnRH ON FERTILITY PARAMETERS IN HAIR GOATS DURING BREEDING SEASON - M. Cinar; A. Ceyhan; O. Yilmaz; H. Erdem (Journal of Animal and Plant Sciences, 2017)
The present study was performed to determine the effect of PGF2α and GnRH injections in different time intervals on fertility in Hair goats during breeding season. Totally, 80 primiparous Hair goats were divided into four groups (n=20 in each) according to the body condition scores of the animals. The animals in groups were treated as follows; first group (Ovsynch), GnRH on day 0, PGF2α on day 7 and GnRH on day 9; second group (2PG-G), PGF2α on day 0, PGF2α on day 7 and GnRH on day 9; third group (PG-G), PGF2α on day 7 and GnRH on day 9; fourth group (G), GnRH on day 9. Bucks were included into the groups on day 10-14 and insemination was performed during standing heat. Blood samples were collected to determine possible embryonic losses on day 21 for further analysis of serum progesterone concentrations. Transabdominal ultrasonography was performed to detect pregnancy on day 40-45. It was determined that in Ovsynch, 2PG-G, PG-G and G groups, estrous rate was 100%, 95%, 95% and 85%; pregnancy rate was 85%, 95%, 95% and 85%; kidding rate was 100%, 78.9%, 94.7% and 88.2%; twinning rate was 41.2%, 40%, 22.2%, 20%; litter size was 1.41, 1.40, 1.22, 1.20, respectively. However, these parameters did not show any significant difference between groups (P> 0.05). In conclusion, it is suggested that all treatment procedures may be used for estrous synchronization in Hair goats during breeding season due to the satisfactory results
Keywords: Goat; Fertility; Synchronization; Ovsynch; GnRH; PGF2α